2018
DOI: 10.1038/s41699-018-0065-3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging nanofabrication and quantum confinement techniques for 2D materials beyond graphene

Abstract: Recent advances in growth techniques have enabled the synthesis of high-quality large area films of 2D materials beyond graphene. As a result, nanofabrication methods must be developed for high-resolution and precise processing of these atomically thin materials. These developments are critical both for the integration of 2D materials in complex, integrated circuitry, as well as the creation of sub-wavelength and quantum-confined nanostructures and devices which allow the study of novel physical phenomena. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 162 publications
(211 reference statements)
2
115
0
Order By: Relevance
“…Engineering the structure and morphology of atomically thin layers (2D materials) is receiving tremendous attention due to both fundamental and applied interest . The quantum confinement effects can yield drastic and unprecedented changes in the physical properties of 2D layers . It is found that the nature and the position of Dirac cone in graphene, the indirect‐to‐direct bandgap transition, and the spin–orbit coupling of transition metal dichalcogenides (TMDs) are tunable by controlling the morphology.…”
Section: Comparison Of Tafel Slopes Of Triangles and Dendritesmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineering the structure and morphology of atomically thin layers (2D materials) is receiving tremendous attention due to both fundamental and applied interest . The quantum confinement effects can yield drastic and unprecedented changes in the physical properties of 2D layers . It is found that the nature and the position of Dirac cone in graphene, the indirect‐to‐direct bandgap transition, and the spin–orbit coupling of transition metal dichalcogenides (TMDs) are tunable by controlling the morphology.…”
Section: Comparison Of Tafel Slopes Of Triangles and Dendritesmentioning
confidence: 99%
“…[1] The quantum confinement effects can yield drastic and unprecedented changes in the physical properties of 2D layers. [2] It is found that the nature and the position of Dirac cone in graphene, [3] the indirect-to-direct bandgap transition, [4] and the spin-orbit coupling of transition metal dichalcogenides (TMDs) [5] are tunable by controlling the morphology. Through this, structure and morphology control of TMDs can have high impact on their electronic, [6] optical, [7] and photo-/electrocatalytic properties.…”
mentioning
confidence: 99%
“…10,11 Defects can strongly influence the electronic properties of MoS 2 . 12,13 Atomic vacancies, interstitials, and grain boundaries have been extensively studied in MoS 2 . Of particular relevance to this work, sulfur vacancies are generally present in single-layer MoS 2 upon synthesis, 14 and they can be induced by processes such as ion beam exposure, [15][16][17][18][19] plasma exposure, [20][21][22][23][24][25] and annealing, 26 to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the functionalization is reversible and amenable to nanofabrication allowing patterning via conventional lithography or tip‐based nanofabrication like heating or friction . Bringing these capabilities together, the combination of patterning and tailoring compound 2D materials are critical to creating 2D integrated systems such as atomically thin electronic circuits, lab‐on‐a‐chip (LOC), and chemically patterned nanotemplates for future transparent, wearable, flexible, and stretchable technologies.…”
mentioning
confidence: 99%